TINJAUAN PENGGUNAAN BERBAGAI BAHAN LIMBAH BERBASIS TUMBUHAN SEBAGAI PEREMAJA TERHADAP SIFAT REOLOGI BITUMEN HASIL EKSTRASI MATERIAL RAP - Indah Handayasari; Putranto, Leksmono S; Subagio, Bambang Sugeng; Najid, Najid (Construction and Material Journal, 2025)
Sustainable innovation in road construction encourages the use of recycled materials, such as Reclaimed Asphalt Pavement/RAP, as an alternative to reduce dependence on new materials and minimize negative environmental impacts. However, RAP materials generally undergo an aging process that causes a decrease in viscoelastic properties, an increase in stiffness, and a decrease in resistance to cracking and deformation. To address these issues, rejuvenators produced from biomass waste - such as rice husks, bagasse, palm oil waste, and other agricultural residues - are being developed as environmentally friendly solution in restoring the rheological properties of RAP asphalt and improving the performance of the asphalt mixture. The results show that plant-based rejuvenators containing lignin with a chemical structure consisting of carbon, hydrogen, oxygen elements, and have active groups such as aromatic ring structures, aliphatic and aromatic hydroxyl groups, and quinone groups very similar in structure to asphalt can rebalance the proportion of malten and asphaltene fractions in aged asphalt. The use of bio-rejuvenators provides performance that results in a decrease in the complex modulus (G⁎) value and an increase in the phase angle (δ), indicating improved flexibility and reduced stiffness of the asphalt, approaching the characteristics of new asphalt. Furthermore, the addition of biojuvenators also positively impacts resistance to rutting and fatigue, while enhancing the workability of the asphalt mixture, especially in low-temperature applications.